Fundamental and excited states of F-type centres in MgSiO3 perovskite - Stashans, A. (2010)
Quantum-chemical modelling based on the HartreeFock methodology and a periodic supercell model is done to study oxygen vacancy and F-type centres in the perovskite-type MgSiO3 crystal. The equilibrium geometry of defects is obtained, confirming the importance of electrostatic interaction in determination of atomic shifts. The calculated relaxation energies due to the defect formation are between 8 and 10 eV, thus evidencing favourability in the occurrence of such defects. The wave functions describing both F+ and F centres are rather diffuse and the point defects are not well localised within the oxygen vacancy region. The ? SCF computed absorption energies due to the F-type centres fall well within the ultraviolet spectrum, between 136 and 254 nm for the F+ centre and between 163 and 248 nm for the F centre. © 2010 Elsevier B.V. All rights reserved.